Sodium-Glucose Cotransporter-2 Inhibitors in Diabetic Patients with Heart Failure: An Update - Nicia I. Profili; Roberto Castelli; Antonio Gidaro; Roberto Manetti; Margherita Maioli; Alessandro P. Delitala (MDPI AG, 2024)
Diabetes mellitus and heart failure are two diseases that are commonly found together, in particular in older patients. High blood glucose has a detrimental effect on the cardiovascular system, and worse glycemic control contributes to the onset and the recrudesce of heart failure. Therefore, any specific treatment aimed to reduce glycated hemoglobin may, in turn, have a beneficial effect on heart failure. Sodium-glucose cotransporter-2 inhibitors have been initially developed for the treatment of type 2 diabetes mellitus, and their significant action is to increase glycosuria, which in turn causes a reduction in glucose blood level and contributes to the reduction of cardiovascular risk. However, recent clinical trials have progressively demonstrated that the glycosuric effect of the sodium-glucose cotransporter-2 inhibitors also have a diuretic effect, which is a crucial target in the management of patients with heart failure. Additional studies also documented that sodium-glucose cotransporter-2 inhibitors improve the therapeutical management of heart failure, independently by the glycemic control and, therefore, by the presence of diabetes mellitus. In this review, we analyzed studies and trials demonstrating the efficacy of sodium-glucose cotransporter-2 inhibitors in treating chronic and acute heart failure.